DOES REBRANDING AS NAME CHANGE REBUILD OR DESTROY BRAND EQUITY (CUSTOMER LOYALTY AND BRAND REPUTATION) AFTER BRAND CRISIS?:THE CASE OF MALAYSIAN AIRLINE SYSTEM (MAS). - Ahmad, Roslizawati; Worlu, Okechukwu (Journal of Technology Management and Business, 2019)
This paper explored on the effect of logo redesigned on rebranding based on consumer perception and acceptance of old logo and new logo after redesigning in Malaysia telecommunication sector. The purpose of this research paper is to identify the effect of logo redesignon rebranding, the relationship between redesigned and rebranding.Thestudy utilizedquantitative survey method of secondary source ingathering data from 375 respondents of student and staff,from three different universities of northern region of Malaysia. Seven Likert scale was used to measure the perception and degree of acceptance of the selected telecommunication new logo. Statistical Package for the Social Sciences (SPSS) 20.0 was used to analyse the collected data. This research paper found significant relationship between logo shape and typography logo redesigning and rebranding,and significant relationship between logo shape, typography logoredesigning and consumerperception. It also established that consumer significantly perceived logo redesigned to be effective and supportive key factor to organization rebranding exercise.This paper presents significant theoretical contribution for academic knowledge purpose and practical contributions for practitioners,in making clear decisions before embarking on rebranding exercise.